Fun with Fives - Hammelef, Danielle S; rushworth, vicki; shen, lynn (Pelham, New York Benchmark Education Company,llc, 2007)
This book demonstrates how grouping items by fives makes counting faster
Arithmetic Notions
1
Keywords: Mathematics; (3GdQjGVjGJs